2019
DOI: 10.1016/j.virol.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Vascular permeability in the brain is a late pathogenic event during Rift Valley fever virus encephalitis in rats

Abstract: Rift Valley fever virus (RVFV) is a zoonotic disease of livestock that causes several clinical outcomes in people including febrile disease, hemorrhagic fever, and/or encephalitis. After aerosol infection with RVFV, Lewis rats develop lethal encephalitic disease, and we use this as a model for studying disease mechanisms of RVFV infection in the brain. Permeability of the brain vasculature in relation to virus invasion and replication is not known. Here, we found that vascular permeability in the brain occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Our previous study found that RVFV vRNA was detectable in the OB as early as 1-2 days p.i., depending upon exposure dose [19,20]. This finding suggests that the olfactory region plays a part in CNS infection, as the virus encounters the respiratory and olfactory epithelium during inhalation.…”
Section: Inhalational Exposure To Rvfv Causes Extensive Infection Of mentioning
confidence: 94%
See 2 more Smart Citations
“…Our previous study found that RVFV vRNA was detectable in the OB as early as 1-2 days p.i., depending upon exposure dose [19,20]. This finding suggests that the olfactory region plays a part in CNS infection, as the virus encounters the respiratory and olfactory epithelium during inhalation.…”
Section: Inhalational Exposure To Rvfv Causes Extensive Infection Of mentioning
confidence: 94%
“…Our previous studies have characterized the Lewis rat model of RVF encephalitis, in which rats exposed to aerosolized RVFV succumb to meningoencephalitis within 7-8 days post-infection (p.i.) [19,20]. By 1 day p.i., viral RNA (vRNA) can be detected at low levels in the brain along with a transient inflammatory leukocyte infiltration [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the peripheral blood biomarkers during the course of the neurological disease in African green monkeys were measured with defect in early T-cells, proinflammatory and antiviral responses in lethal encephalitis [79]. Other immune disorders and alteration in vascular permeability in the brain could be more involved in delayed forms [80].…”
Section: Meningoencephalitismentioning
confidence: 99%
“…Wistar-Furth and Brown Norway rats are highly susceptible and succumb to acute hepatitis regardless of the infection route (18), while August-Copenhagen-Irish rats skew toward encephalitis (19). Conversely, RVF manifestations in Lewis rats are highly dependent on route of infection: subcutaneously infected animals develop viremia but no disease signs (18), while aerosol exposure leads to uniformly lethal encephalitis (17,20,21). Syrian hamsters develop acute liver disease following subcutaneous exposure to RVFV and have also been used to evaluate vaccines and therapeutics against RVFV (22)(23)(24).…”
mentioning
confidence: 99%